LIKA-LIKU KEHIDUPAN PAK SEP DALAM NOVEL TARIAN OMBAK KARYA GERSON POYK - Jacob, Angelina Melany (Humanis; Volume 6. No. 2. Februari 2014, 2014)
The object in this research is "Tarian Ombak" which is written by Gerson Poyk. This novel was selected because the main character has dominant psychology descriptions that have inner pressure continuously, so he always tried to get out from the situation. The issue in this research has been focused on how the psychology aspect of the main character in the "Tarian Ombak" novel. The structure of personality theory from Sigmund Freud had been chosen as a basic theory in this research. Analysis result from the main character “Pak Sep” in the novel "Tarian Ombak" show that he has a good personality in problem solving, because he can be handle the matter through him superego.
Keywords: main character, personality, psychology.